Selective area epitaxy by metalorganic chemical vapor deposition– a tool for photonic and novel nanostructure integration. (January 2021) - Dapkus, P. Daniel; Chi, Chun Yung; Choi, Sang Jun; Chu, Hyung Joon; Dreiske, Mitchell; Li, Rijuan; Lin, Yenting; Nakajima, Yoshitake; Ren, Dawei; Stevenson, Ryan; Yao, Maoqing; Yeh, Ting Wei; et al.
Abstract: Selective area epitaxial (SAE) growth of III-V materials and devices by metalorganic chemical vapor deposition is selectively reviewed to illustrate the concepts employed in this technology and its most relevant applications. Special focus on the use of SAE use for photonic integration, heterogeneous integration of materials relevant to photonic integration, and nanostructure integration is made. Throughout, the pioneering work led by Professor James J. Coleman is used to illustrate the value of using selective growth for various applications.